Metastatic Parotid Myoepithelial Carcinoma in a 7-Year-Old Boy - Issam Saliba; Nazir El Khatib; Antoine Nehme; Selim Nasser; Nabil Moukarzel (Case Reports in Pediatrics)
Myoepithelial carcinoma is a rare malignancy of the parotid gland that is usually seen in adults. We report the first case in children of myoepithelial carcinoma of the parotid gland with massive invasion of the facial nerve and metastasis to cervical lymph nodes. Due to its rarity, the treatment and the clinical course of this tumor are not well defined yet. We performed a total parotidectomy, a modified neck dissection, and a postoperative radiotherapy in 7-year-old boy. Sparing of the facial nerve was impossible; it was sacrificed and grafted with a sural nerve. Histopathology confirmed the diagnosis of a parotid gland carcinoma and immunohistochemical markers showed that the tumor cells express cytokeratin, epithelial membrane antigen, cytokeratin 7, smooth muscle actin, P63, CEA, and S100. This pattern of immunostaining is consistent with the diagnosis of myoepithelial carcinoma. On the postoperative tenth month he presented with a pulmonary and lumbar vertebra metastasis.